UJI POTENSI AKTIVITAS ANTI KANKER EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Dede Sukandar; Sandra Hermanto; Emi Lestari (Jurnal Kimia Terapan Indonesia, 2009)
Has been done research to know anticancerpotencial activity from fragrant screw pine leaf extractapplies method Brine Shrimp Lethality Test ( BSLT).Extract is made by the way of macerate to apply threekinds of solvent, that is butanol, ethyl acetate, and etherpetroleum. Toxicity test is done by using prawn larvaArtemia salina Leach which age 48 hours. Toxic effecteach extract is identified with presentase death of prawnlarva applies probit analysis (LC50). Active extract thenis tested its the phytochemistry content and compoundbioa1(fi! suggested applies GC-MS. Result of his (itsshowing ethyl acetate extract to have the character oftoxic ( LC50 : 288,4 ppm). The toxic compounds whichpredietion.implied in ethyl acetate extract is terpenoidsand steroid.Keywords: Fragrant Screw Pine Leaf Extract, BSLT, Artemiasalina LFitokimia, and GC-MS